2006
DOI: 10.21273/hortsci.41.2.329
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High Tunnel and Field Conditions on Strawberry Growth and Development

Abstract: Plant growth, yield, and fruit quality of two strawberries (Fragaria ×ananassa Duch.)—`Chandler' and `Sweet Charlie'—grown under high tunnels (HTs) were compared with that of field plants during 2002–03 and 2003–04 growing seasons. Plug plants were planted in mid-October 2002 and mid-September 2003 on raised beds covered with black polyethylene mulch. Microclimate of the HTs protected strawberry crowns from winter damage and advanced fruit productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 13 publications
2
70
0
1
Order By: Relevance
“…Plants produced berries 5 weeks earlier than the open-field counterparts with 41-54°F warmer soil conditions. Size of berry, soluble solids content, yields, branch-crown development, and plant vigor were greater within the tunnel (Kadir et al, 2006a).…”
Section: High Tunnel Production Systemsmentioning
confidence: 90%
See 4 more Smart Citations
“…Plants produced berries 5 weeks earlier than the open-field counterparts with 41-54°F warmer soil conditions. Size of berry, soluble solids content, yields, branch-crown development, and plant vigor were greater within the tunnel (Kadir et al, 2006a).…”
Section: High Tunnel Production Systemsmentioning
confidence: 90%
“…High tunnels add to the productivity of the crop when utilized for protection from wind, birds, and harsh weather, while minimizing disease pressure with less moisture on foliage (Phelps, 2014). Kadir et al (2006a) observed success with June-bearing strawberries grown in Kansas high tunnels in regards to yield, plant growth, and fruit quality. The high tunnel production method incorporated black plastic mulch, and raised beds.…”
Section: High Tunnel Production Systemsmentioning
confidence: 92%
See 3 more Smart Citations